FAKTOR-FAKTOR PENDORONG REMAJA DALAM MELESTARIKAN KESENIAN KUDA LUMPING DI DESA GAJING KAHEAN KECAMATAN GUNUNG MALIGAS KABUPATEN SIMALUNGUN - Triana, Windi; Marnelly, Tengku Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in Gajing Kahean Gunung Maligas Sub District Simalungun Regency, the purpose of this research is to know and analyze The Thrust Factors Teenager In Conserving Kuda Lumping Art In Gajing Kahean Gunung Maligas Sub District Simalungun Regency. This research is Qualitative research which analyzed descriptively, and instrument of data is observation and interview. The theory used in this research is Fungcional theory. In this study of informants there are eight people and three support informant. Sampling technique is Purposive Sampling. The result of the research on the informants explained that The Development of Kuda Lumping Art in the Gajing Kahean from past to now has Experienced a Change in Costume, Musical Instruments and Dance Moves. The Thrust Factors Teenagers In Conserving Kuda Lumping Art is The First is Intern Factor Consisting Of The Young Desire to Follow the Art is Based on Personal will. Secondary From Family is The Urge from The Family to Participate in the Art. While External Factor there are two of Our Friends and Environment. The Values Contained in this Art are three, Religy Value, Moral Value, Integrationist Value and Recreation Value.The Keys : Kuda Lumping Art, Teenagers, The Thrust Factors